The Vocabulary of Vision in Euripides’ Medea and in Seneca’s Medea: A Comparative Study (Circe de clásicos y modernos, 2020)
This paper intends to make a comparative study of the vocabulary related to the semantic field of the sense of vision in Euripides’ Medea and in Seneca’s Medea. We consider that this issue is of a prominent relevance in both tragedies, due to the high frequency of the explicit mention of these words. The aim is to analyze comparatively which implications these terms have in both plays, in order to examine to what extent they can provide a key for reading each of them. The hypothesis is that the vocabulary related to the sense of vision has a different dramatic function in these tragedies. Specifically, this implies a distinct configuration of the main character as a tragic character, and this may as well shed light on the global understanding of these plays.
Keywords: vocabulary; vision; Medea; Euripides; Seneca